Estimating the level and distribution of global household wealth - James B. Davies; Susanna Sandström; Anthony Shorrocks; Edward N. Wolff (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
We provide the first estimate of the level and distribution of global household wealth. Mean assets and debts within countries are measured, partly or wholly, for 38 countries using household balance sheet and survey data centred on the year 2000. Determinants of mean financial assets, non-financial assets, and liabilities are studied empirically, and the results are used to impute values to countries lacking wealth data. Household wealth per adult is US43,494 in PPP terms, and ranges regionally from US11,655 in Africa to US193,147 in North America. Data on the shape of the household distribution of wealth for 20 countries, accounting for 59 per cent of the world's population and, we estimate, 84 per cent of its wealth are used to establish patterns of wealth inequality within countries. Imputations are again performed for countries lacking wealth data, on the basis of the observed relation between wealth and income distribution for the 20 countries with data. The Gini coefficient for the global distribution of wealth is 0.804, and the share of the top 10 per cent is 71 per cent. Wealth of US8,325 is needed to be in the top half of the distribution, and US517,601 is needed to be in the top one per cent. Between-country differences in wealth are two-thirds of global inequality according to the Gini coefficient, indicating a larger role for within-country inequality than in the case of income according to recent estimates. – wealth ; net worth ; personal assets ; inequality ; households ; balance sheets ; portfolios
Keywords: D31; E01; E21; O10; 330; Vermögen; Vermögensverteilung; Welt